SISTEM DERIVASI (الإشتقاق) DALAM BAHASA ARAB DAN URGENSINYA DALAM PENGAJARAN BAHASA - Akhyar Hanif (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2012)
Derivation is a model for linguistic study in Arabic which is not only important to be introduced to Arabic Department students but also urgent in teaching Arabic, especially in Islamic colleges/universities such as STAIN, IAIN, and UIN to widen students’ horizon and develop Arabic teaching system itself as well. Furthermore, one of the functions of derivational system or al-istiqaq is as a medium for reproducing new vocabularies (lexis). This should be realized and considerably important in response to stigmatization found in Arabic teaching where Arabic is believed as the language of religion and therefore did not develop and change.Kata kunci: derivasi, urgensi, pengajaran bahasa Arab